A comparative study on oxidative and antioxidative markers of serum and follicular fluid in GnRH agonist and antagonist cycles - Celik, Ebru; Celik, Onder; Kumbak, Banu; Yilmaz, Ercan; Turkcuoglu, Ilgin; Simsek, Yavuz; Tanbek, Kevser (Springer/Plenum Publishers, 2012)
To determine whether concentrations of oxidative stress markers of follicular fluid and serum are different in GnRH agonist protocol from GnRH antagonist protocol. This was a cross-sectional study. Eighty-four women undergoing controlled ovarian stimulation with either GnRH agonist (n = 39) or GnRH antagonist protocols (n = 45) for IVF/ICSI treatment were assigned by a physician. Blood was obtained at the time of oocyte retrieval, and follicular fluid (FF) from the mature follicles of each ovary was centrifuged and frozen until analysis. Malondialdehyde (MDA), nitric oxide (NO), protein carbonyl (PC), hydroxyl proline (OH-P), sodium oxide dismutase (SOD), reduced glutathione (GSH), glutathione peroxidase (GSH-Px), adenosine deaminase (ADA) and xanthine oxidase (XO) were assessed in the serum and follicular fluid of each participants. The mean serum concentrations of GSH-Px, GSH and MDA were lower in the GnRH antagonist group compared to GnRH agonist group, but mean serum SOD was higher in the GnRH antagonist group. The mean follicular SOD, ADA and NO were higher in GnRH antagonist group than GnRH agonist group. The IVF/ICSI outcomes were similar in both groups. GnRH antagonist protocol is associated with increased oxidative stress. The relation of GnRH analogues with oxidative stress and its implication in follicular growth needs to be addressed in further studies.
Keywords: Oxidative stress; GnRH antagonist; GnRH agonist; IVF/ICSI